Mapping of potential work-related musculoskeletal disorders in Junrejo community health center - Bayu Prastowo; Ananda Hanny; Danang Dwi Prayudho (Journal of Community Service and Empowerment, 2023)
The International Labor Organization states that controlling work-related musculoskeletal disorders (WMSDs) is part of the Sustainable Development Goals (SDGs) program to protect labour rights and promote a work environment according to the concept of Ergonomic Function Deployment (EFD). This study aims to map the potential for WMSDs in the Junrejo Community Health Center environment. The study used the Nordic Body Map (NBM) questionnaire presented using data triangulation. The NBM results showed an average score of 32.54. This value informs that workers in the Junrejo community health centre environment have a low risk of WMSDs or do not yet need priority action.